The tropospheric 14CO2 level in mid latitudes of the Northern Hemisphere (1959-2003) - Levin, Ingeborg; Kromer, Bernd (Universitätsbibliothek der Universität Heidelberg, 2004)
A comprehensive tropospheric 14CO2 data set of quasi-continuous observations covering the time span from 1959 to 2003 is presented. Samples were collected at three European mountain sites at height levels of 1205m (Schauinsland), 1800m (Vermunt) and 3450 m a.s.l. (Jungfraujoch), and analysed in the Heidelberg Radiocarbon Laboratory. The data set from Jungfraujoch (1986-2003) is considered to represent the free tropospheric background level at mid latitudes of the Northern Hemisphere as it compares well with recent (yet unpublished) measurements made at the marine baseline station Mace Head (west coast of Ireland). The Vermunt and Schauinsland records are significantly influenced by regional European fossil fuel CO2 emissions. The respective Delta14CO2 depletions, on an annual mean basis, are, however, only less than 5 permil compared to Jungfraujoch. The Vermunt and Schauinsland sites are considered to represent well the mean continental European troposphere.
Wissenschaftl. Aufsatz. - Aus: Radiocarbon Vol 46(2004) No 3, Seiten 1261-1271